Empowerement and Development on The North Coast of East Java - Handini, Sri (Universitas Dr. Soetomo, 2019)
This study aims to describe: to find out development and empowerment, obstacles in empowerment, the role of government in empowering MSMEs on the north coast of East Java, and strategies for empowering MSMEs to face the ASEAN free market. This study uses a descriptive qualitative approach. Technical data analysis is used with the Miles and Huberman model where the data analysis process is 3 periods, namely data reduction (data reduction), data display (data presentation), and verification (conclusion drawing). Triangulation is used as a data validity technique in which in this study the triangulation used is triangulation of sources. The results of the study show that: (1) the process of community development and empowerment includes (a) increased skills and independence of the community, (b) there are impacts from social, economic, and education, (2) inhibiting factors including different community characteristics and thoughts, constrained by readiness HR, people's understanding is still low. (3) the role of the government, namely by participation and involvement in community empowerment. (4) Strategies in developing coastal areas, namely the community economy.